The Provisions of the Accused's Confession - Dr. Faraj Muhammad Al-Tayeb (Journal of Scientific and Human Dimensions, 2026)
This study includes what is related to recognition, whether by a comprehensive explanation of its concept, types, and the nature of the law, as well as the conditions set for it, as well as the authority before which it is issued, as well as its forms, and its sections, as this study included a detail of the explicit of the confession, and that what distinguishes this is its issuance of a free will, and away from any kind of coercion, whether material or moral, and the study included a topic of great importance with regard to the court's authority to make a confession, that it relies on a confession. The accused at any stage of the investigation until he is reassured, and the confession may be excluded, under specific conditions, and it may be annulled under the conditions specified by the law
Keywords: Recognition; Proof; Accused; Judicial; Criminal; Nullity; Coercion-Free Will; Discretion; Threat; Influence; Silence